L2, a chloroplast metalloproteinase, regulates fruit ripening by participating in ethylene autocatalysis under the control of ethylene response factors. (13th July 2021) - Li, Guobin; Wang, Jiafa; Zhang, Chunli; Ai, Guo; Zhang, Dedi; Wei, Jing; Cai, Liangyu; Li, Changbao; Zhu, Wenzhao; Larkin, Robert M; Zhang, Junhong
Abstract : Mutation of chloroplast metalloprotease gene L2 causes tomato immature fruit to turn white and delays ripening. L2 is involved in autocatalytic ethylene biosynthesis during fruit ripening and is regulated by ERF transcription factors. Abstract: Although autocatalytic ethylene biosynthesis plays an important role in the ripening of climacteric fruits, our knowledge of the network that promotes it remains limited. We identified white fruit ( wf ), a tomato mutant that produces immature fruit that are white and that ripen slowly. We found that an inversion on chromosome 10 disrupts the LUTESCENT2 ( L2 ) gene, and that white fruit is allelic to lutescent2 . Using CRISPR/Cas9 technology we knocked out L2 in wild type tomato and found that the l2-cr mutants produced phenotypes that were very similar to white fruit ( lutescent2 ). In the l2-cr fruit, chloroplast development was impaired and the accumulation of carotenoids and lycopene occurred more slowly than in wild type. During fruit ripening in l2-cr mutants, the peak of ethylene release was delayed, less ethylene was produced, and the expression of ACO genes was significantly suppressed. We also found that exogenous ethylene induces the expression of L2 and that ERF.B3, an ethylene response factor, binds to the promoter of the L2 gene and activates its transcription. Thus, the expression of L2 is regulated by exogenous ethylene. Taken together, our results indicate that ethylene may affect the expression of L2 gene and that L2 participates in autocatalytic ethylene biosynthesis during tomato fruit ripening.